Effect of endosulfan, HCH, copper and zinc on the phototactic and swimming rate of larvae of the mangrove crab Macrophthalmus erato De Man. - Kannupandi, T; Pasupathi, K; Soundarapandian, P (Indian Journal of Fisheries, 2011)
The different contaminants tested, altered the positive phototactic response andswimming rate of M. erato larvae. Positive phototactic response was observedonly in the early period of study, ranging from 6 to 12 h under endosulfan, HCH,copper and zinc stress. A negative phototactic response, followed by no responsewas observed at later stage of toxicity tests. The severity in the impairment ofthe response was more pronounced in the highest test concentration. Swimmingrate decreased during exposure to endosulfan, HCH, copper and zinc in differentzoeal stages of development. Decreased swimming rate was directly related totest concentrations.